Super-wear-resistant thermoplastic elastomer composite material for automotive trim and preparation method of super-wear-resistant thermoplastic elastomer composite material
By improving the formulation and production process of thermoplastic elastomers and combining with the special twin screw granulation process, the problem of insufficient wear and scratch resistance of existing thermoplastic elastomers for automotive interior decoration has been solved, and the material's wear and scratch resistance is improved and the production cost is reduced.
Patent Information
- Application Number
- CN202411975028.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing thermoplastic elastomer materials for automotive interiors have poor wear and scratch resistance, and it is difficult to replace genuine leather, imitation leather and sieve PVC.
By improving the formulation and production process of thermoplastic elastomers, raw materials such as styrene-based elastomer substrates, surface-modified wear-resistant agents, plasticizers, compatibilizers and polyamide-based elastomers are used, and combined with a special twin-screw granulation process, the wear-resistant characteristics of the material are improved.
It significantly improves the wear and scratch resistance of thermoplastic elastomer materials, meets the temperature, weather and odor requirements of automotive interiors, reduces production costs, and improves production efficiency.
Smart Images

Figure BDA0005220254190000051 
Figure BDA0005220254190000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer modification, in particular to a super wear-resistant thermoplastic elastomer composite material for automobile interior decoration and a preparation method thereof. Background Art
[0002] At present, the proportion of soft-touch materials in automobile interiors is increasing. Such soft materials can provide good visual and tactile feelings. The following categories are mainly suitable for the production of soft-touch materials for automobile interiors: 1. Leather wrapping; 2. Imitation leather wrapping; 3. Enamel PVC wrapping; 4. Vacuum TPO wrapping; 5. Two-color injection molding. Among them, leather and imitation leather wrapping have the disadvantages of high cost, low material utilization rate, and long processing cycle; Enamel PVC wrapping has the disadvantages of high energy consumption, long molding cycle, poor odor and environmental performance; Vacuum TPO wrapping has low cost, but low material utilization rate, hard feel, and no rubber texture; two-color injection molding process has good processing efficiency, good touch and appearance, and low material cost and processing cost, which is a major direction for the development of automobile interiors in the future. However, this type of thermoplastic elastomer has an obvious disadvantage, that is, the material has poor wear resistance and scratch resistance. Compared with genuine leather, imitation leather, and slush PVC, the wear resistance and scratch resistance are not enough. If the wear resistance and scratch resistance of thermoplastic elastomers can be solved, then this type of material will have a further application in automotive interiors.
[0003] There is little research data on the wear resistance of thermoplastic elastomers at home and abroad. Among them, China's public patent document CN202410943592 discloses a highly wear-resistant thermoplastic elastomer foam material for shoes and a preparation method thereof, comprising the following raw materials in parts by weight: 100 parts of SBS; 20-40 parts of polystyrene; 20-30 parts of cyclohexane oil; 10-20 parts of additives; 8-15 parts of ethylene-acrylic acid copolymer; 1-4 parts of foaming agent; 0.5-2 parts of antioxidant; 0.5-2 parts of light stabilizer; 0.4-2 parts of foam nucleating agent; 0.2-1 parts of release agent; 0.02-0.06 parts of cross-linking agent. China's public patent document CN20202010166967 discloses a highly wear-resistant thermoplastic elastomer, which includes, by weight: thermoplastic elastomer: 100-130 parts, polystyrene PG-22: 18-30 parts; impact polystyrene HIPS: 25-40 parts; resistant agent FZ-600: 2-12 parts; ethylene-vinyl acetate copolymer EVA: 0.6-3 parts; calcium carbonate 1003C: 3-12 parts; antioxidant 1076: 0.1-1 parts; anti-ultraviolet agent: 0.1-1.5 parts; cyclic oil: 15-30 parts. The above two invention patent materials can be applied to shoe materials, but because the invention patents use more materials with poor temperature resistance, weather resistance, and odor resistance, the invention is not suitable for automotive soft touch interior products. Summary of the invention
[0004] The main purpose of the present invention is to provide a super wear-resistant thermoplastic elastomer composite material for automobile interior and a preparation method thereof, which overcomes the shortcomings of the prior art, improves the wear resistance of the thermoplastic elastomer material by improving the formula of the thermoplastic elastomer and improving the production process, and at the same time meets the requirements of automobile interior temperature resistance, weather resistance and odor, so that it can be used for automobile interior soft touch materials, replacing genuine leather, imitation leather, and slush PVC coating processes, greatly reducing the cost of automobile interior and improving interior production efficiency.
[0005] In order to achieve the above purpose, the technical solution adopted by the present invention is:
[0006] A super wear-resistant thermoplastic elastomer composite material for automobile interior, the raw materials of which include, by weight: 100 parts of styrene elastomer matrix; 10-50 parts of surface modified wear-resistant agent; 10-80 parts of plasticizer; 2-20 parts of compatibilizer; 10-50 parts of polyamide elastomer; and 0.5-5 parts of antioxidant and anti-ultraviolet additive.
[0007] In one embodiment of the present invention, the raw materials include, by weight: 100 parts of styrene elastomer matrix; 20 parts of surface modified wear-resistant agent; 50 parts of plasticizer; 10 parts of compatibilizer; 20 parts of polyamide elastomer and 2.5 parts of antioxidant and anti-ultraviolet additive.
[0008] In one embodiment of the invention, the styrene elastomer is selected from one or a combination of SBS (styrene-butadiene-styrene triblock copolymer), SIS (styrene-isoprene-styrene triblock copolymer), SEBS (hydrogenated styrene-butadiene-styrene triblock copolymer), SEPS (hydrogenated styrene-isoprene-styrene triblock copolymer), and SEEPS (hydrogenated styrene-ethylene-isoprene-styrene block copolymer).
[0009] According to an embodiment of the present invention, the surface modified wear-resistant agent is one or a combination of metal sulfide, metal oxide, and nitride surface modified by a silane coupling agent.
[0010] According to one embodiment of the present invention, the metal sulfide is one or a combination of bismuth sulfide, cuprous sulfide, zinc sulfide, molybdenum disulfide, tungsten disulfide, and stannous sulfide; the metal oxide is one or a combination of aluminum oxide, tungsten oxide, and zirconium oxide; the nitride is one or a combination of silicon nitride and molybdenum nitride.
[0011] According to one embodiment of the present invention, the raw materials for preparing the surface modified wear-resistant agent are: 20-60 parts of molybdenum disulfide, preferably with a particle size of 500 mesh, 20-60 parts of aluminum oxide, preferably with a particle size of 500 mesh, and 0.5-1.5 parts of silane coupling agent.
[0012] According to one embodiment of the present invention, the plasticizer is ultra-high viscosity paraffin oil, the kinematic viscosity of the paraffin oil at 40°C is not less than 80 mm2 / s, the flash point is not less than 270°C, and the CP value is greater than 65%.
[0013] According to an embodiment of the present invention, the solubilizer is one or a combination of maleic anhydride grafted polypropylene, maleic anhydride grafted POE, maleic anhydride grafted SEBS, and glycidyl methacrylate grafted POE.
[0014] According to an embodiment of the present invention, the polyamide elastomer is selected from one or more of hardness 80A, 90A, 40D, 50D, and 60D.
[0015] According to one embodiment of the present invention, the antioxidant and anti-ultraviolet agent are selected from one or more of 1010, 1076, 1330, 1024, 168, 626, DLTDP, UV531, UV326, UV328, UV329, UV234, UV770, UV944, and UV622.
[0016] A method for preparing a super wear-resistant thermoplastic elastomer composite material for automobile interior, comprising the steps of:
[0017] S100: Evenly mix the corresponding weight portions of styrene elastomer matrix, plasticizer, compatibilizer, polyamide elastomer, and antioxidant and anti-ultraviolet agent by a high-speed mixer or a coloring machine, and the mixing time is ≥30 minutes;
[0018] S200: After the mixed raw materials are left to stand for 24 hours, the corresponding weight portion of surface modification and wear resistance agent is added, and the mixture is mixed with a coloring machine for 5-10 minutes until it is completely mixed;
[0019] According to one embodiment of the present invention, the preparation method of the surface modified wear-resistant agent further includes the steps of: S300 adding the wear-resistant agent powder into a horizontal stirring barrel and stirring evenly, spraying the silane coupling agent and ethanol mixture through a sprayer, stirring while spraying evenly, and after the corresponding weight of the silane coupling agent and ethanol mixture is sprayed, continue stirring for 3-6 hours and then take it out for use.
[0020] According to one embodiment of the present invention, the temperature of the coloring machine in step S100 is 20-80°C, and the mixing speed is 10-500r / min, the temperature of the coloring machine in step S200 is 20-80°C, and the mixing speed is 10-500r / min, and the temperature of the horizontal mixer in step S300 is 50-80°C, and the mixing speed is 5-100r / min.
[0021] According to one embodiment of the present invention, the styrene elastomer in step S100 is selected from one or more of SEBS, SEPS, and SEEPS, preferably a star-shaped high-side group SEBS raw material, with a hydrogenation degree of ≥99%, a weight-average molecular weight of ≥30W, and a 1,2-butadiene content of greater than 50%; the plasticizer is an ultra-high viscosity paraffin oil, and the paraffin oil preferably has a kinematic viscosity of not less than 80 mm2 / s at 40°C, a flash point of not less than 270°C, and a CP value of greater than 65%; the polyamide elastomer preferably has a hardness of 90A and a melt flow rate of 5-10 g / 10 min; the poly-compatibilizer is preferably a maleic anhydride-grafted POE elastomer. The wear-resistant powder in step S300 is a compound of one or more of metal sulfides, metal oxides, and nitrides, preferably molybdenum disulfide and aluminum oxide are compounded in a ratio of 1:1, wherein molybdenum disulfide is a flaky structure and aluminum oxide is a spherical structure, and the silane coupling agent is KH550 or a similar product.
[0022] S400 adds the completely homogenized raw material mixture into a twin-screw granulator for modification and granulation to obtain a super wear-resistant thermoplastic elastomer composite material granule for automotive interior decoration;
[0023] According to one embodiment of the present invention, the twin-screw granulator in step S400 has a screw aspect ratio of 44 to 60, preferably a screw aspect ratio of 52, a screw temperature of 180 to 220° C., preferably 200° C., and a main engine speed of 100 to 800 r / min, preferably 550 r / min.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The ultra-wear-resistant thermoplastic elastomer composite material for automobile interior of the present invention increases the wear resistance of the elastomer by compounding high wear-resistant fillers and high wear-resistant polyamide elastomer materials, improves the bonding force between the wear-resistant fillers and the elastomer by modifying the surface of the wear-resistant fillers, increases the wear resistance of the elastomer under different friction conditions by compounding flaky and spherical wear-resistant fillers, and increases the compatibility between the wear-resistant polyurethane elastomer material and the substrate by adding maleic anhydride grafts, so that the interconducting grid structure is achieved in an ideal state, thereby further improving the wear resistance of the elastomer;
[0026] (2) The styrene elastomer substrate of the present invention adopts hydrogenated styrene-butadiene-styrene triblock copolymer, which has ultra-high molecular weight, high proportion of side groups, high degree of hydrogenation and star-shaped structure, and further improves the wear resistance of the material;
[0027] (3) The paraffin oil used is ultra-high viscosity paraffin oil, which has high kinematic viscosity and flash point, less volatile matter, less heat loss at high temperature, improved product production stability, and is suitable for the strict odor and VOC requirements of automotive interior products;
[0028] (4) The present invention adopts a special twin-screw equipment with a high aspect ratio, small screw gap and good processing stability. The finished material has high mechanical properties and temperature and weather resistance, and has excellent processing performance, which can meet the production and processing requirements of automotive interiors. DETAILED DESCRIPTION
[0029] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0030] As used herein, the term "prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0031] When amount, concentration or other value or parameter is represented by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing range "1 to 5", the described range should be interpreted as including range "1 to 4", "1 to 3", "1-2", "1-2 and 4-5", "1-3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the range is intended to include its end value and all integers and fractions within the range.
[0032] "Polymer" means a polymeric compound prepared by polymerizing monomers, whether of the same or a different type. The generic term "polymer" embraces the terms "homopolymer," "copolymer," "terpolymer," and "interpolymer."
[0033] Example 1
[0034] A super wear-resistant thermoplastic elastomer composite material for automobile interior decoration, the raw materials are calculated by weight: 100 parts of styrene elastomer matrix; 20 parts of surface modified wear-resistant agent; 50 parts of plasticizer; 10 parts of compatibilizer; 20 parts of polyamide elastomer and 2.5 parts of antioxidant and anti-ultraviolet additive.
[0035] Among them, the styrene elastomer is selected from one or more of SEBS, SEPS, and SEEPS, preferably a star-shaped high-side group SEBS raw material, with a hydrogenation degree ≥99%, a weight-average molecular weight ≥30W, and a 1,2-butadiene content greater than 50%; the plasticizer is ultra-high viscosity paraffin oil, and the paraffin oil preferably has a kinematic viscosity of not less than 80mm2 / s at 40°C, a flash point of not less than 270°C, and a CP value greater than 65%; the polyamide elastomer preferably has a hardness of 90A and a melt flow rate of 5-10g / 10min; the polycompatibilizer is preferably a maleic anhydride grafted POE elastomer.
[0036] The preparation method of the surface modified wear-resistant agent comprises the following steps:
[0037] (1.a) Add the corresponding weight portion of anti-wear agent matrix into a horizontal mixing barrel and stir evenly. The temperature of the horizontal mixer is 50-80°C and the mixing speed is 5-100r / min;
[0038] (1.b) Spray the silane coupling agent and ethanol mixture through a sprayer, stirring while spraying evenly;
[0039] (1.C) After the corresponding weight of the silane coupling agent and ethanol mixture is sprayed in, continue stirring for 3-6 hours and then take it out for use.
[0040] The wear-resistant powder is a compound of one or more of metal sulfides, metal oxides and nitrides, preferably molybdenum disulfide and aluminum oxide are compounded in a ratio of 1:1, wherein molybdenum disulfide is a flaky structure and aluminum oxide is a spherical structure, and the silane coupling agent and ethanol mixture is a mixture of KH550 or a similar product and ethanol in a weight ratio of 1:1.
[0041] A method for preparing a super wear-resistant thermoplastic elastomer composite material for automobile interior, comprising the steps of:
[0042] (1) Mix the corresponding weight portions of styrene elastomer matrix, plasticizer, compatibilizer, polyamide elastomer, and antioxidant and anti-ultraviolet agent by a high-speed mixer or a coloring machine for ≥30 min;
[0043] (2) After the mixed raw materials are left to stand for 24 hours, a corresponding weight portion of surface modification and wear resistance agent is added, and the mixture is mixed with a coloring machine for 5-10 minutes until the mixture is completely mixed;
[0044] (3) adding the completely homogenized raw material mixture into a twin-screw granulator for modification and granulation to obtain ultra-wear-resistant thermoplastic elastomer composite material particles for automotive interior decoration;
[0045] The twin-screw granulator has a screw aspect ratio of 44 to 60, preferably 52, a screw temperature of 180 to 220° C., preferably 200° C., and a main engine speed of 100 to 800 r / min, preferably 550 r / min.
[0046] Embodiment 2-6
[0047] The preparation method and application method of Examples 2-6 are the same as those of Example 1, and the formula ratio is adjusted as shown in Table 1.
[0048] Table 1: Formula ratio of Examples 2-12
[0049]
[0050]
[0051] Comparative Example 1
[0052] A super wear-resistant thermoplastic elastomer composite material for automobile interior, the raw materials are calculated by weight: 100 parts of styrene elastomer matrix; 20 parts of unmodified wear-resistant agent; 50 parts of plasticizer; 10 parts of compatibilizer; 20 parts of polyamide elastomer and 2.5 parts of antioxidant and anti-ultraviolet additive.
[0053] Among them, the styrene elastomer is selected from one or more of SEBS, SEPS, and SEEPS, preferably a star-shaped high-side group SEBS raw material, with a hydrogenation degree of ≥99%, a weight-average molecular weight of ≥30W, and a 1,2-butadiene content of greater than 50%; the plasticizer is an ultra-high viscosity paraffin oil, and the paraffin oil preferably has a kinematic viscosity of not less than 80mm2 / s at 40°C, a flash point of not less than 270°C, and a CP value of greater than 65%; the polyamide elastomer preferably has a hardness of 90A and a melt flow rate of 5-10g / 10min; the polycompatibilizer is preferably a maleic anhydride grafted POE elastomer. The unmodified wear-resistant agent is a compound of one or more metal sulfides, metal oxides, and nitrides, preferably molybdenum disulfide and aluminum oxide are compounded in a ratio of 1:1, wherein molybdenum disulfide is a flaky structure and aluminum oxide is a spherical structure.
[0054] A method for preparing a super wear-resistant thermoplastic elastomer composite material for automobile interior, comprising the steps of:
[0055] (1) Mix the corresponding weight portions of styrene elastomer matrix, plasticizer, compatibilizer, polyamide elastomer, and antioxidant and anti-ultraviolet agent by a high-speed mixer or a coloring machine for ≥30 min;
[0056] (2) After the mixed raw materials are left to stand for 24 hours, a corresponding amount of unmodified anti-wear agent is added, and the mixture is mixed with a coloring machine for 5-10 minutes until the mixture is completely mixed;
[0057] (3) adding the completely homogenized raw material mixture into a twin-screw granulator for modification and granulation to obtain ultra-wear-resistant thermoplastic elastomer composite material particles for automotive interior decoration;
[0058] The twin-screw granulator has a screw aspect ratio of 44 to 60, preferably 52, a screw temperature of 180 to 220° C., preferably 200° C., and a main engine speed of 100 to 800 r / min, preferably 550 r / min.
[0059] Comparative Example 2
[0060] A super wear-resistant thermoplastic elastomer composite material for automobile interior, the raw materials are calculated by weight: 100 parts of styrene elastomer matrix; 50 parts of plasticizer; 10 parts of compatibilizer; 20 parts of polyamide elastomer and 2.5 parts of antioxidant and anti-ultraviolet additive. The preparation method is the same as that of comparative example 1, except that the raw material content of the wear-resistant agent is different, wherein the amount of the wear-resistant agent is 0 parts.
[0061] Comparative Example 3
[0062] The preparation method of Comparative Example 3 is the same as that of Comparative Example 2, except that the raw material content of the compatibilizer is different, wherein the amount of the compatibilizer is 0 parts.
[0063] Comparative Example 4
[0064] The preparation method of Comparative Example 4 is the same as that of Comparative Example 3, except that the raw material content of the polyamide elastomer is different, wherein the amount of the polyamide elastomer is 0 parts.
[0065] Comparative Example 5
[0066] The preparation method of Comparative Example 5 is the same as that of Comparative Example 4, except that the raw material type of the styrene elastomer substrate is different, wherein the styrene elastomer is linear SEBS with a weight average molecular weight of ≤15W.
[0067] Performance Testing:
[0068] The tensile strength at break is tested according to ISO37 standard, the strip is type 2, and the tensile speed is 500mm / min; the tear strength is tested according to ISO34-1 standard, the strip is a right-angle tearing strip, and the tensile speed is 500mm / min; the hardness is tested according to ISO868 standard, and the reading time is 15S; the cross scratch is tested according to PV3952 standard, the weight is 10N, and the scraper is 1mm; the odor is tested according to PV1303 standard, the temperature is 80℃, the time is 2 hours, and the 6-level evaluation is performed, and the lower the level, the better; the wear resistance is tested according to GWT A L50-01 standard, Taber abrasion machine, load 1kg, number of revolutions 2000r, 5-level evaluation, and the higher the level, the better. Three samples of the material are tested, and the average value is taken. The performance test results of Examples 1 to 6 are shown in Table 2.
[0069] Table 2 Performance test results of Example 1N6
[0070] Performance Project Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Shore hardness (A) 70 69 73 68 75 70 Tensile strength(MPa) 9.9 9.6 10.4 8.5 8.8 6.7 Elongation at break (%) 676 689 556 505 446 316 Tear strength (KN / m) 38 36 30 29 38 24 Odor(level) 3.5 3.5 4.0 3.5 4.0 3.5 Cross scratch (ΔE) 0.9 1.1 1.2 1.3 0.7 2.6 Wear resistance test (grade) 4 3.5 4.2 3.6 4.4 3
[0071] The performance test results of Comparative Examples 1 to 5 are shown in Table 3.
[0072] Table 3 Performance test results of comparative examples 1 to 5
[0073]
[0074]
[0075] From the performance comparison of the above-mentioned Examples 1, 2, 3 and Comparative Examples 1, 2, it can be seen that the present invention increases the scratch resistance and wear resistance of the material by adding the surface modified wear agent. When the amount of the surface modified wear agent added is within an appropriate range, the material cross scratch test has a qualified result, meeting the automotive interior ΔE≤1.5, and the wear resistance test can reach the requirement of ≥4 levels. This is because the surface modified wear agent is evenly dispersed in the material and on the surface, and fits tightly in the polymer material. Due to the effect of the silane coupling agent, the inorganic wear agent and the organic polymer are bonded. The combination is further strengthened. In the wear resistance and scratch resistance test summary, the wear-resistant agent plays a role in supporting the substrate and resisting friction, which significantly improves the wear resistance of the material. However, when the amount of surface modified wear-resistant agent added is too much, the basic mechanical properties of the material will drop sharply, the odor level of the material will increase, and it may even fail to meet the requirements of automotive interior decoration. This is because too much surface modified wear-resistant agent destroys the continuity and consistency of the elastomer substrate. In addition, since the odor of the silane coupling agent is relatively strong, the increase in the amount of silane coupling agent causes the odor to be unqualified. From the above Examples 1, 4, 5, 6 and Comparative Examples 3, 4 From the performance comparison, it can be seen that the addition of the compatibilizer and the polyamide elastomer improves the mechanical properties and the scratch and wear resistance of the material. This is because the polyamide elastomer itself has very strong molecular cohesive energy due to the presence of the amide group, and has certain self-lubricating properties, and its wear resistance is very good. The addition of the polyamide elastomer improves the wear and scratch resistance of the styrene-based elastomer to a certain extent. However, since the polyamide elastomer is a polar material, it itself has poor compatibility with the non-polar styrene elastomer. When the amount of the compatibilizer is small or not added, the presence of the polyamide elastomer is equivalent to destroying the consistency of the styrene elastomer, resulting in poor mechanical properties and a decrease in wear and scratch resistance. Since the polyamide elastomer has a high hardness and a strong odor, when the amount added is too much, the hardness and odor do not meet the requirements of automotive interior decoration. From the performance comparison of the above Example 1 and Comparative Example 5, it can be seen that the star-shaped, high molecular weight, and high side group content SEBS significantly improves the mechanical properties and wear and scratch resistance of the material. This is because the star-shaped material has many cross-linking points, which is helpful for wear resistance. In addition, the high molecular weight and high side group content increase the molecular cohesive energy and increase the strength. The thermoplastic elastomer prepared by adding surface modified wear-resistant agent, increasing polyamide elastomer and using special styrene elastomer has excellent mechanical properties, enhanced wear resistance and scratch resistance, and the odor meets the requirements of automobile interior. The prepared elastomer material can be used in automobile interior products with wear resistance requirements.
[0076] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A super wear-resistant thermoplastic elastomer composite material for automobile interior, characterized in that: The raw materials include, by weight: 100 parts of styrene elastomer matrix; 10-50 parts of surface modified wear-resistant agent; 10-80 parts of plasticizer; 2-20 parts of volume extender; 10-50 parts of polyamide elastomer; and 0.5-5 parts of antioxidant and anti-ultraviolet additive.
2. The ultra-wear-resistant thermoplastic elastomer composite material for automobile interior decoration according to claim 1, characterized in that: The raw materials include, by weight: 100 parts of styrene elastomer matrix; 20 parts of surface modified wear-resistant agent; 50 parts of plasticizer; 10 parts of compatibilizer; 20 parts of polyamide elastomer and 2.5 parts of antioxidant and anti-ultraviolet additive.
3. The ultra-wear-resistant thermoplastic elastomer composite material for automobile interior decoration according to claim 1, characterized in that: The styrene elastomer is selected from one or a combination of SBS (styrene-butadiene-styrene triblock copolymer), SIS (styrene-isoprene-styrene triblock copolymer), SEBS (hydrogenated styrene-butadiene-styrene triblock copolymer), SEPS (hydrogenated styrene-isoprene-styrene triblock copolymer), SEEPS (hydrogenated styrene-ethylene-isoprene-styrene block copolymer).
4. The ultra-wear-resistant thermoplastic elastomer composite material for automobile interior decoration according to claim 1, characterized in that: The surface modified wear-resistant agent is one or a combination of metal sulfide, metal oxide and nitride surface modified by a silane coupling agent.
5. The ultra-wear-resistant thermoplastic elastomer composite material for automobile interior decoration according to claim 4, characterized in that: The metal sulfide is one or a combination of bismuth sulfide, cuprous sulfide, zinc sulfide, molybdenum disulfide, tungsten disulfide, and stannous sulfide; the metal oxide is one or a combination of aluminum oxide, tungsten oxide, and zirconium oxide; the nitride is one or a combination of silicon nitride and molybdenum nitride.
6. The ultra-wear-resistant thermoplastic elastomer composite material for automobile interior decoration according to claim 1, characterized in that: The raw materials for preparing the surface modified wear-resistant agent are: 20-60 parts of molybdenum disulfide with a particle size of 500 mesh; 20-60 parts of aluminum oxide with a particle size of 500 mesh; and 0.5-1.5 parts of a silane coupling agent.
7. The ultra-wear-resistant thermoplastic elastomer composite material for automobile interior decoration according to claim 1, characterized in that: The plasticizer is ultra-high viscosity paraffin oil, the kinematic viscosity of the paraffin oil at 40° C. is not less than 80 mm 2 / s, the flash point is not less than 270° C., and the CP value is greater than 65%.
8. The ultra-wear-resistant thermoplastic elastomer composite material for automobile interior decoration according to claim 1, characterized in that: The solubilizer is one or a combination of maleic anhydride grafted polypropylene, maleic anhydride grafted POE, maleic anhydride grafted SEBS, and glycidyl methacrylate grafted POE.
9. The ultra-wear-resistant thermoplastic elastomer composite material for automobile interior decoration according to claim 1, characterized in that: The polyamide elastomer is selected from one or more of hardness 80A, 90A, 40D, 50D, and 60D.
10. The ultra-wear-resistant thermoplastic elastomer composite material for automobile interior decoration according to claim 1, characterized in that: The antioxidant and anti-ultraviolet agent are selected from one or more of 1010, 1076, 1330, 1024, 168, 626, DLTDP, UV531, UV326, UV328, UV329, UV234, UV770, UV944, and UV622.
11. The method for preparing the super wear-resistant thermoplastic elastomer composite material for automobile interior decoration according to any one of claims 1 to 10, characterized in that: It includes the steps of: S100: Evenly mix the corresponding weight portions of styrene elastomer matrix, plasticizer, compatibilizer, polyamide elastomer, and antioxidant and anti-ultraviolet agent by a high-speed mixer or a coloring machine, and the mixing time is ≥30 minutes; S200: After the mixed raw materials are left to stand for 24 hours, the corresponding weight portion of surface modification and wear resistance agent is added, and the mixture is mixed with a coloring machine for 5-10 minutes until it is completely mixed; S300: Add the wear-resistant agent powder into the horizontal mixing barrel and stir evenly, spray the silane coupling agent and ethanol mixture through the sprayer, stir evenly while spraying, continue stirring for 3-6 hours after the corresponding weight of the silane coupling agent and ethanol mixture is sprayed, and then take it out for use; S400 adds the completely homogenized raw material mixture into a twin-screw granulator for modification and granulation to produce a super wear-resistant thermoplastic elastomer composite material granule for automobile interior.
12. The method for preparing the super wear-resistant thermoplastic elastomer composite material for automobile interior according to claim 11, characterized in that: The temperature of the coloring machine in step S100 is 20-80°C, and the mixing speed is 10-500r / min. The temperature of the coloring machine in step S200 is 20-80°C, and the mixing speed is 10-500r / min. The temperature of the horizontal mixer in step S300 is 50-80°C, and the mixing speed is 5-100r / min.
13. The method for preparing the super wear-resistant thermoplastic elastomer composite material for automobile interior according to claim 11, characterized in that: In step S100, the styrene elastomer is selected from one or more of SEBS, SEPS, and SEEPS; the polycompatibilizer is maleic anhydride grafted POE elastomer; the plasticizer is ultra-high viscosity paraffin oil; the wear-resistant powder in step S300 is a composite of one or more of metal sulfides, metal oxides, and nitrides, and the silane coupling agent is KH550 or a similar product.
14. The method for preparing the super wear-resistant thermoplastic elastomer composite material for automobile interior according to claim 13, characterized in that: The hydrogenation degree of the styrene elastomer is ≥99%, the weight average molecular weight is ≥30W, and the 1,2-butadiene content is greater than 50%; the paraffin oil preferably has a kinematic viscosity of not less than 80mm2 / s at 40°C, a flash point of not less than 270°C, and a CP value greater than 65%. The polyamide elastomer preferably has a hardness of 90A and a melt flow rate of 5-10g / 10min; the wear-resistant powder is a compound of molybdenum disulfide and aluminum oxide in a ratio of 1:1, wherein molybdenum disulfide has a flaky structure and aluminum oxide has a spherical structure.
15. The method for preparing the super wear-resistant thermoplastic elastomer composite material for automobile interior decoration according to claim 11, characterized in that: In step S400, the twin-screw granulator has a screw length-to-diameter ratio of 44 to 60, a screw temperature of 180 to 220° C., and a main engine speed of 100 to 800 r / min.
16. The method for preparing the super wear-resistant thermoplastic elastomer composite material for automobile interior decoration according to claim 15, characterized in that: In step S400, the twin-screw granulator has a screw length-to-diameter ratio of 52, a screw temperature of 200° C., and a main engine speed of 550 r / min.
Citation Information
Patent Citations
Wear-resistant thermoplastic elastomer and preparation method thereof
CN101845195A
High-wear-resistant polypropylene composite material used for automobile interior trim and preparation method of polypropylene composite material
CN107488301A
Scratch-resistant halogen-free flame-retardant elastomer, and preparation method and application thereof
CN113861658A